Establishment of kinetic parameters of particle reaction from a well-stirred fluidized bed reactor. (15th October 2015) - Haustein, H.D.; Kreitzberg, T.; Gövert, B.; Massmeyer, A.; Kneer, R.
Abstract: A novel method is presented for experimental study of gas-particle reactions, based on realizing a well-stirred reactor as a small scale fluidized bed. This reactor is evaluated against the drop tube reactor and the thermo-gravimetric analyser. It shows to enable high heat up rates (∼10 4  K/s), long timescale observation (up to several hours), operation with small fuel particles (∼100 μm) and accurate control of reaction conditions. Char reaction rates are established from real-time gas product analysis by FTIR spectroscopy, through a detailed data-analysis procedure. This procedure employs a particle surface-evolution model and accounts for sampling system signal attenuation. The validity of the well-stirred conditions is established, and the method is employed for char combustion and gasification. Highly consistent results for char gasification over a wide range of conditions ( T  = 800–1100 °C, C CO 2  = 19–76%), are used to demonstrate the establishment of kinetic parameters for an n -th order approach. Activation energy and order of reaction are found and compare well with the literature.